2011
DOI: 10.1186/1471-2458-11-786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an electronic nicotine delivery device (e-Cigarette) on smoking reduction and cessation: a prospective 6-month pilot study

Abstract: BackgroundCigarette smoking is a tough addiction to break. Therefore, improved approaches to smoking cessation are necessary. The electronic-cigarette (e-Cigarette), a battery-powered electronic nicotine delivery device (ENDD) resembling a cigarette, may help smokers to remain abstinent during their quit attempt or to reduce cigarette consumption. Efficacy and safety of these devices in long-term smoking cessation and/or smoking reduction studies have never been investigated.MethodsIn this prospective proof-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
309
4
17

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(357 citation statements)
references
References 29 publications
17
309
4
17
Order By: Relevance
“…sore/dry mouth or throat and cough) are often reported in the literature. 14,17,28,29 This finding is not surprising as aerosol propylene glycol and glycerin, the primary ingredients of e-liquid, are associated with mouth and throat irritation. It is possible that these side effects would eventually diminish (half the participants had been using e-cigarettes for at most 14 months at the time of the survey).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…sore/dry mouth or throat and cough) are often reported in the literature. 14,17,28,29 This finding is not surprising as aerosol propylene glycol and glycerin, the primary ingredients of e-liquid, are associated with mouth and throat irritation. It is possible that these side effects would eventually diminish (half the participants had been using e-cigarettes for at most 14 months at the time of the survey).…”
Section: Discussionmentioning
confidence: 83%
“…It is possible that these side effects would eventually diminish (half the participants had been using e-cigarettes for at most 14 months at the time of the survey). 16,29 Some respondents reported potentially more serious health effects-4 noted heart palpitations and 3 reported chest pain. In a summary of adverse events potentially related to e-cigarettes, Chen 28 noted that chest pain and rapid heartbeat have been reported to the Food and Drug Administration.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst surveys and small scale clinical studies suggest successful replacement of smoking with e-cigarettes due to the presence of nicotine (Dawkins et al, 2013;Etter & Bullen, 2011;Polosa et al, 2011;Siegel, Tanwar & Wood, 2011), effects of vaping on blood nicotine levels are relatively unexplored. In the current study, a significant increase in plasma nicotine level was observed 10 mins after taking 10 puffs on the e-cigarette (from 0.74 ng/ml to 6.77 ng/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst surveys of users and small scale clinical studies suggest their potential for smoking cessation and harm 4 reduction (Caponneto et al, 2013;Dawkins et al, 2013;Etter & Bullen, 2011;Polosa et al, 2011) their ability to deliver nicotine is under-explored.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 However, longitudinal analysis using population-level data found no difference in quit rates between e-cigarette users and nonusers. 9 Controlled clinical trials and populationlevel observational cohort studies are needed to establish the utility of these cigarettes to facilitate smoking cessation.…”
Section: Potential Health Benefits For Individual Smokersmentioning
confidence: 99%